Parameter identification of a network attack to a rational distribution of resources protection - Данилина, Г. В.; Милокум, Я. В.; Безвершенко, Э. И. (Problems of Informatization and Control, 2010)
For continuous estimation of the parameters and the network status in real-time network is considered as a discrete dynamical system with lumped parameters. Turn-based parameter identification and state of the network based on the discrete Kalman filter reduces to solving the problem of estimating the correlation matrix and the transition matrix of the system